Spatial distribution of dengue in Honduras during 2016–2019 using a geographic information systems (GIS)–Dengue epidemic implications for public health and travel medicine. Issue 32 (November 2019) - Zambrano, Lysien I.; Rodriguez, Edith; Espinoza-Salvado, Iván Alfonso; Fuentes-Barahona, Itzel Carolina; Lyra de Oliveira, Tales; Luciano da Veiga, Glaucia; Cláudio da Silva, José; Valle-Reconco, Jorge Alberto; Rodríguez-Morales, Alfonso J.
Abstract: Background: After serious epidemics of chikungunya (CHIKV) and Zika (ZIKV) in the Americas, dengue (DENV) have reemerged in most countries. We analyzed the incidence, incidence rates, and evolution of DENV cases in Honduras from 2015 to 2018 and the ongoing 2019 epidemic. Methods: Using epidemiological weeks (EW) surveillance data on the DENV in Honduras, we estimated incidence rates (cases/100, 000 population), and developed maps at national, departmental, and municipal levels. Results: From January 1, 2016 to July 21, 2019, a total of 109, 557 cases of DENV were reported, 28, 603 in 2019, with an incidence rate of 312.32 cases/100, 000 population this year; 0.13% laboratory-confirmed. The highest peak was reached on the EW 28°, 2019 (5299 cases; 57.89 cases/100, 000 population). The department with the highest number of cases and incidence rate was Cortes (8404 cases, 479.68 cases/100, 000 population in 2019). Discussion: The pattern and evolution of DENV epidemic in 2019 in Honduras has been similar to that which occurred for in 2015. As previously reported, this epidemic involved the north and central areas of the country predominantly, reaching municipality incidences there >1000 cases/100, 000 population (or 1%). Studies using geographical information systems linked with clinical disease characteristics are necessary to obtain accurate epidemiological data for public health systems. Such information is also useful for assessment of risk for travelers who visit specific areas in a destination country.